Crystal structure of (3R,3aS,6R,6aR)-6-hexyl-3-methyltetrahydrofuro[3,4-b]furan-2,4-dione, C13H20O4 - Huang Yu-Xi; Chen Zan-Hong; Liao Yu-Ting; Li Jia-Yi; Huang Mei-Ying; Ding Bo; Huang Hong-Bo; Tao Yi-Wen (Zeitschrift für Kristallographie - New Crystal Structures)
C13H20O4, monoclinic, P21 (no. 4), a = 9.7071(4) Å, b = 7.9026(4) Å, c = 17.3139(7) Å, β = 101.617(4)°, V = 1300.97(10) Å3, Z = 4, Rgt(F) = 0.0428, wRref (F 2) = 0.1145, T = 170 K.